1956
DOI: 10.1099/00221287-15-2-261
|View full text |Cite
|
Sign up to set email alerts
|

Non-identity of the Phospholipase of Bacillus anthracis with the Anthrax Toxin

Abstract: Filtrates from suitable cultures of Bacillus anthracis contain a phospholipase which slowly hydrolyses the phospholipid in egg-yolk broth but has no action on free egg-lecithin. This enzyme does not appear to be the anthrax toxin. McGaughey & Chu (1948) showed that Bacillus anthracis produced an opalescence when growing in a medium containing egg yolk, but the effect was less than that produced by B. cereus and B. mycoides. B. anthracisgrowing in the blood of infected guinea-pigs produces an extracellular tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1958
1958
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Transcript was detected for plcB, smcA, and plcA in vitro during B. anthracis infections of cultured macrophages (15). In addition, plasma from guinea pigs dying of anthrax displayed higher levels of PLC activity versus culture filtrates of B. anthracis, implying that they may play a role in the disease (45). Recently, it was shown by ectopic expression of each B. anthracis PLC gene in Escherichia coli and L. monocytogenes that the genes encode functional proteins with activities similar to their corresponding B. cereus orthologues (25,40).…”
mentioning
confidence: 96%
“…Transcript was detected for plcB, smcA, and plcA in vitro during B. anthracis infections of cultured macrophages (15). In addition, plasma from guinea pigs dying of anthrax displayed higher levels of PLC activity versus culture filtrates of B. anthracis, implying that they may play a role in the disease (45). Recently, it was shown by ectopic expression of each B. anthracis PLC gene in Escherichia coli and L. monocytogenes that the genes encode functional proteins with activities similar to their corresponding B. cereus orthologues (25,40).…”
mentioning
confidence: 96%
“…Attempts to produce antisera in rabbits, guinea pigs, and rats were unsuccessful. Zwartouw and Smith (1956) found that filtrates of the NP strain of B. anthracis hydrolyzed the phospholipid in egg-yolk broth but not free egg lecithins or cephalins. Their preparations did not hemolyze guinea pig red blood cells and did not produce a skin reaction in guinea pigs.…”
mentioning
confidence: 98%
“…The possibility that lecithinase has a role in the disease of anthrax has not been extensively investigated. Zwartouw and Smith (1956) stated that B. anthracis culture filtrates hydrolyzed phospholipid in egg yolk broth but did not hydrolyze free egg lecithin and that the phospholipase was not anthrax toxin. Preliminary toxicity tests performed with lecithinase from an avirulent strain have indicated that B. anthracis lecithinase was nontoxic to mice and that it may not be a contributing factor in the damage of 1958]…”
Section: Discussionmentioning
confidence: 99%